2020
DOI: 10.24127/ajpm.v9i4.3049
|View full text |Cite
|
Sign up to set email alerts
|

Meta Analisis: Pengaruh Problem-Based Learning Terhadap Kemampuan Literasi Matematis Siswa Di Indonesia Tujuh Tahun Terakhir

Abstract: Hingga saat ini ratusan kajian tentang kemampaun literasi matematis siswa telah disajikan dalam bentuk literatur yang didukung oleh penggunaan model Problem Based Learning (PBL). Dalam literatur terdapat banyak laporan dengan temuan yang bervariasi. Studi meta-analisis ini dilakukan untuk memeriksa efek keseluruhan penggunaan model PBL terhadap kemampuan literasi matematis siswa dan mendeteksi tingkat variasi antar studi. Database ERIC, SAGE, SpringerLink, dan Google Cendekia diperiksa untuk mencapai penelitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
10
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 18 publications
7
10
0
4
Order By: Relevance
“…The current research shows that PBL has a positive impact on students' creative thinking in mathematics. This study's effect size is consistent with previous studies' findings (e.g., Susanti et al, 2020;Paloloang et al, 2020), but the findings of this study contribute to the literature on study characteristics that need to be considered in implementing PBL. Although it has been suggested that teachers need convincing information regarding PBL implementation, this finding is based only on the primary studies that met the inclusion criteria.…”
Section: Findings and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current research shows that PBL has a positive impact on students' creative thinking in mathematics. This study's effect size is consistent with previous studies' findings (e.g., Susanti et al, 2020;Paloloang et al, 2020), but the findings of this study contribute to the literature on study characteristics that need to be considered in implementing PBL. Although it has been suggested that teachers need convincing information regarding PBL implementation, this finding is based only on the primary studies that met the inclusion criteria.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…This finding is in line with the results of Susanti, Juandi, and Tamur (2020), who found an effect size of 0.79 when they synthesized the results from 12 articles comparing the effectiveness of PBL on mathematical communication skills. Similar results were found by Paloloang et al (2020), who found an effect size of 0.83 when they analyzed the results of 14 articles comparing the effectiveness of PBL on students' mathematical literacy abilities. However, this study's overall size is different from the results of Asror's (2016) study, which reported an effect size of 0.51 when he analyzed the impact of PBL on students' creative mathematical thinking.…”
Section: Findings and Discussionsupporting
confidence: 83%
“…It indicates that the characteristics of the sample size do not significantly lead to heterogeneity in the effect sizes of the whole studies in this meta-analysis study. This result was similar to the previous MA study that the sample size characteristics did not cause the heterogeneity of the effect size of the studies conducted in the meta-analysis process (Demirel & Dağyar, 2016;Suparman et al, 2021;Yunita et al, 2020;Paloloang et al, 2020).…”
Section: B Analysis Of the Study Characteristicssupporting
confidence: 90%
“…This research has followed that stage. This stage has been implemented by other researchers in the field of education, for example (Turgut & Turgut, 2018;Paloloang et al, 2020;Suparman et al, 2021;Susanti et al, 2020;Yunita et al, 2020;Suparman, Tamur, et al, 2021;Tamur, Kusumah, et al, 2021;Sari et al, 2021). This research has also followed these stages which are detailed as follows:…”
Section: Methodsmentioning
confidence: 99%